Method of test for determination of the ignitability of solid electrical insulating materials when exposed to an electrically heated wire source (BSI, 1991)
Solid electrical insulating materials, Electrical insulating materials, Fire tests, Temperature, Ignitability, Test specimens, Dimensions, Specimen preparation, Test equipment